More Cargoes : 1897 - Jacobs, W. W. (William Wymark), 1863-1943 (Salt Lake City, UT : Project Gutenberg, 2008)
"More Cargoes" by W. W. Jacobs is a collection of humorous short stories written in the late 19th century. The book features a variety of engaging narratives centered around maritime adventures and the eccentric characters commonly found in seafaring life. Notable characters include a young lad named Ralph, who embarks on a fanciful first voyage on a ship that he believes to be a pirate vessel. The opening of "More Cargoes" introduces readers to Ralph, a fourteen-year-old boy full of confidence and grand ideas, as he interacts with a rough light porter and a waterman while trying to get to his ship, the "Susan Jane". He confidently navigates conversations, believing he has a comprehensive understanding of seafaring. The light-hearted tone is set as Ralph surprisingly creates tensions with the adults around him, showcasing his youthful bravado and the humor of adults' reactions to his naiveté. The scene establishes an atmosphere filled with wit and comedic misunderstandings, indicating that this collection will explore the quirkiness of life at sea through engaging storytelling. (This is an automatically generated summary.)
Smoked skipper -- A safety match -- A rash experiment -- The cabin passenger -- "Choice spirits" -- A disciplinarian -- Brother Hutchins -- The disbursement sheet -- Rule of three -- Pickled herring -- Two of a trade -- An intervention -- The grey parrot -- Money changers -- The lost ship.
Release date is 2008-06-12
David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; River life -- Fiction